Untangling human neurogenesis to understand and counteract brain disorders. (February 2020) - Beckervordersandforth, Ruth; Rolando, Chiara
Abstract : Neurogenesis in the human postnatal brain occurs in two regions, the subventricular zone of the later ventricle and the dentate gyrus of the hippocampus. While it is well accepted that SVZ and hippocampal neurogenesis are active during juvenile stages in human, their contribution during adulthood and ageing as well as pathological states is recently animating the neural stem cell research field. In this review we will discuss recent evidence about the organization of SVZ and hippocampal neurogenic niches, and will report on how human adult neurogenesis may contribute to disease and appears to respond to neurodegeneration. In light of these novel findings, we will discuss how we can target human adult neurogenesis in order to influence brain disease trajectories.